Investigation on the bandgap of semiconductor solid solution Hg₁₋x₋y₋zCdxMnyZnzTe - Zhikharevich, V.V.; Ostapov, S.E.; Deibuk, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The paper presents a investigation on the bandgap of a new narrow-gap semiconductor solid solution Hg₁₋x₋y₋zCdxMnyZnzTe via optical measurements. Modeling of the edge of fundamental absorption for Hg₁₋x₋y₋zCdxMnyZnzTe is performed and specifying values of the bandgap at room temperature in crystals under study are determined.